Implementing Stack E6 via OS Linux Sockets - Zaitsev, Dmitry A; M.A., Kharsun (Journal of Advanced Computer Science & Technology, 2012)
New software implementation of Ukrainian national stack of networking protocols E6 was presented. Within operating system Linux kernel, families of E6 protocols and addresses were created as well as functions of their processing, in the form of a loadable module. Application of socket technology gives a series of considerable advantages among which unified with other stacks application interface, reuse of the kernel resources facilitating the further development and enterprise implementation of stack E6, engineering corresponding networking devices.